Strategies for Promoting Lifestyles in Families and Communities - U. O, Okoye (Journal of Home Economics Research, 2024)
Lifestyles include everything individuals and families do. These include the food, clothing, goods and services they consume, even their patterns of interaction, and so on. Lifestyles are part of each individual’s identity and a major concern for health and wellbeing. This paper focuses on the concept of lifestyle, changing lifestyles, and sustainable lifestyles. It also reviews the strategies for achieving sustainable lifestyles. The vital role of government in promoting sustainable lifestyles among individuals, families and communities is also explored.